Perspectives ebook - Pilkey, Dav (Cat Kid Comic Club, 2021)
Cat Kid Comic Club is back in session in this groundbreaking graphic novel narrative by Dav Pilkey, the worldwide bestselling and award-winning author and illustrator of Dog Man. Flippy, Molly, Li'l Petey, and twenty-one baby frogs each have something to say. Naomi and Melvin don't see eye to eye and Poppy perceives the world differently than her siblings. Will the baby frogs figure out how to work together and appreciate one another's point of view — both inside and outside the classroom? The shenanigans are nonstop and the baby frogs' minicomics are funny and full of heart. Creating stories within a story, author and illustrator Dav Pilkey uses a variety of techniques — including acrylic paints, colored pencils, Japanese calligraphy, photography, collage, gouache, watercolors, and much more — to portray each frog's perspective. The kaleidoscope of art styles, paired with Pilkey's trademark storytelling and humor, fosters creativity, collaboration, independence, and empathy. Readers of all ages will relish this joyful graphic novel adventure.